MECHANISMS OF LEGAL RESPONSE AND SOCIAL PROTECTION ON THE FACTS OF DOMESTIC VIOLENCE ACCORDING TO CURRENT LEGISLATION OF GEORGIA - Shetekauri, Mindia (European Scientific Journal, ESJ, 2015)
Domestic violence in itself is one of the most difficult, specific and wide-spread social-legal problems containing the number of signs of violation. Conflict directly concerns people connected with coexistence; it has the local, exclusive character and the fight against it is less effective in accordance with common practice of fight against the crime. Specificity of the fight against the crime of this category is expressed in both complexity of its revealing and in effective and lawful choice of coercive measures against it. The issue of domestic violence has been tabooed in many countries for a long time, because the disclosure of such issues was considered as interference in people’s private life. Although the society has gradually realized that the problem of domestic violence must not be ignored as violence endangers people’s health and life. Domestic violence is not only the problem of separate individuals, it has negative effect on the other members of the family, especially on minors and leads to distortion of their psyche and consciousness which, in its turn, leads to the formation of an unhealthy situation in the society.